2015
DOI: 10.3168/jds.2014-8255
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reproductive management programs using lift chart analysis and cost-sensitive evaluation of classification errors

Abstract: The common practice on most commercial dairy farms is to inseminate all cows that are eligible for breeding, while ignoring (or absorbing) the costs associated with semen and labor directed toward low-fertility cows that are unlikely to conceive. Modern analytical methods, such as machine learning algorithms, can be applied to cow-specific explanatory variables for the purpose of computing probabilities of success or failure associated with upcoming insemination events. Lift chart analysis can identify subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Models can be used (a) to take decisions in complex situations where many variables interact dynamically over time; (b) to analyze the effect of future circumstances on farm performance and profitability; (c) to assess risks and uncertainties through sensitivity analysis; and (d) to make decisions about areas in which little information is available. Many different areas of the dairy production system have already been modeled, such as diseases (Østergaard et al, 2005;Bruijins et al, 2010), reproductive strategies (Giordano et al, 2011(Giordano et al, , 2012Shahinfar et al, 2015), replacement policies (Cabrera, 2010), feeding strategies (Cabrera and Kalantari, 2016), and interactions between genotype and environment (Bryant et al, 2005;Kaniyamattam et al, 2016), among others. However, in most cases, these models are limited to simulate the consequences of 1 specific problem and do not account for the potential interactions with other areas of the farm.…”
Section: Introductionmentioning
confidence: 99%
“…Models can be used (a) to take decisions in complex situations where many variables interact dynamically over time; (b) to analyze the effect of future circumstances on farm performance and profitability; (c) to assess risks and uncertainties through sensitivity analysis; and (d) to make decisions about areas in which little information is available. Many different areas of the dairy production system have already been modeled, such as diseases (Østergaard et al, 2005;Bruijins et al, 2010), reproductive strategies (Giordano et al, 2011(Giordano et al, , 2012Shahinfar et al, 2015), replacement policies (Cabrera, 2010), feeding strategies (Cabrera and Kalantari, 2016), and interactions between genotype and environment (Bryant et al, 2005;Kaniyamattam et al, 2016), among others. However, in most cases, these models are limited to simulate the consequences of 1 specific problem and do not account for the potential interactions with other areas of the farm.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, BCS and milk production provide proxies of underlying diseases that affect fertility in dairy cows. Diseases are known to influence insemination success (Inchaisri et al, 2010a;Shahinfar et al, 2015).…”
mentioning
confidence: 99%
“…These decisions could be economically optimized in a decision support model, such as the model developed by Steeneveld and Hogeveen (2012). Previous work has indicated that the VWP (Inchaisri et al, 2011b), the decision to stop inseminating cows (Inchaisri et al, 2012), and inseminating only a proportion of the herd with the highest chance on insemination success could be optimized economically (Shahinfar et al, 2015). Therefore, the potential exists for economi-cally optimized decision support systems for insemination decisions, which would need a prognostic model like the current model.…”
mentioning
confidence: 99%
“…These decisions could be economically optimized in a decision support model, such as the model developed by . Previous work has indicated that the VWP (Inchaisri, et al, 2011b), the decision to stop inseminating cows (Inchaisri, et al, 2012) and inseminating only a proportion of the herd with the highest chance on insemination success could be optimized economically (Shahinfar, et al, 2015). Therefore, potential for economically optimized decision support systems for insemination decisions, which would need a prognostic model like the current model exists.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been conducted on the economic benefits of improved reproductive performance (Galvão, et al, 2013, Giordano, et al, 2011, Inchaisri, et al, 2010b, Shahinfar, et al, 2015. Firk et al (2002) discussed the use of sensors for estrus detection, with a focus on detection performance and algorithms used.…”
Section: Sensors In Farm Managementmentioning
confidence: 99%